Triglyceride-glucose index for the detection of subclinical heart failure with preserved ejection fraction in patients with type 2 diabetes - Wang, Tingting; Xu, Jiani; Zhang, Hong; Tao, Lichan; Huang, Xiaolin (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The triglyceride-glucose (TyG) index has been identified as a reliable and simple surrogate of insulin resistance. In this study, we sought to determine the association between TyG index and cardiac function among asymptomatic individuals with type 2 diabetes (T2DM) without history of any cardiovascular disease. Materials and Methods: The cross-sectional study enrolled 180 T2DM patients without cardiac symptoms. Heart failure with preserved ejection fraction (HFpEF) was defined as Heart Failure Association (HFA)-PEFF score ≥ 5 points. Results: A total of 38 (21.1%) diabetic patients were identified with HFpEF. Compared with the low-TyG group (TyG index < 9.47), patients in high-TyG group (TyG index ≥ 9.47) showed increased risk of metabolic syndrome and diastolic dysfunction (P < 0.05 for each). Furthermore, after adjustment of confounding variables, the TyG index showed positive correlation with risk factors of metabolic syndrome (including BMI, waist circumference, blood pressure, HbA1c, TG, TC, non-HDL-C, and fasting blood glucose, P < 0.05 for each) and parameters of diastolic dysfunction (E/e’ ratio, P < 0.0001) in patients with T2DM. Moreover, Receiver Operating Characteristic curve analysis showed that the TyG index could be better to predict the risk of suspected HFpEF than other indicators (AUC: 0.706, 95% CI: 0.612-0.801). According, on multiple regression analysis, TyG index was independently correlated with the incidence of HFpEF (odds ratio: 0.786, P = 0.0019), indicating that TyG index could be a reliable biomarker to predict the risk of HFpEF. Conclusions: The TyG index showed a positive correlation with the risk of subclinical HFpEF in patients with T2DM, providing a new marker to predict and treat HFpEF in diabetes.